Community Awareness and Government Response to Cholera Outbreaks in Borno State - Airaoje, Ojemeiri Karl; Akintayo, Atinuke Olubukade; Adewale, Olugbenga Charles; Obada, Aruaye Afeye (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
Cholera remains a major public health concern in many developing regions, particularly in areas affected by conflict, displacement, and inadequate sanitation. Borno State, located in Northeastern Nigeria, has experienced recurrent cholera outbreaks due to a combination of factors, including poor access to clean water, overcrowded internally displaced persons (IDP) camps, and fragile healthcare infrastructure. Young adults (18-30 years) and children under 18 account for the majority of cases, with a slight predominance of females (53%) due to increased water-related activities. This study highlights key outbreak drivers, including contaminated water sources, lack of sanitation facilities, and low awareness of cholera prevention measures. Findings indicate that 48.7% of residents rely on untreated well water, 68.4% lack toilet access, and only 23.5% practice regular handwashing, contributing to recurrent outbreaks. In addition, limited vaccination coverage (22%) and knowledge gaps about cholera transmission and symptoms further increase vulnerability to annual cholera outbreaks. To mitigate future outbreaks, the study recommends improving water supply and treatment, enhancing sanitation infrastructure, and promoting hygiene education. Expanding cholera vaccination campaigns and strengthening community health education initiatives are also critical. Government agencies and public health stakeholders must prioritize these interventions to reduce cholera incidence and improve overall public health resilience in Jere LGA.